EXAMINING THE BENEFITS OF HUMOUR IN NURSING CARE - Amir Ahmad Dar (PT. Radja Intercontinental Publishing, 2023)
Humour, when appropriately incorporated into nursing care, has demonstrated positive effects on patient outcomes and nursing staff well-being. This abstract explores the role of humour in healthcare, focusing on its impact on reducing stress levels, increasing patient satisfaction, and improving emotional well-being. It also investigates the influence of humour on nursing staff morale, job satisfaction, and overall well-being. Incorporating humour into nursing care creates a positive and relaxed atmosphere for patients, leading to reduced stress levels and enhanced patient satisfaction. Humour also uplifts patients' spirits, fostering emotional well-being and improving coping abilities. In terms of nursing staff, humour helps reduce stress and burnout, fosters a positive work environment, and enhances staff camaraderie. Although specific quantitative data on the relationship between humour and staff retention is limited, a positive association between job satisfaction and staff retention in the nursing profession suggests that humour indirectly contributes to higher staff retention rates. Practical strategies for integrating humour into nursing practice include knowing patients' preferences, using light-hearted conversations, sharing humorous stories, and employing visual humour. By embracing these strategies, nurses can create a positive and engaging healthcare environment, benefiting both patients and nursing staff.